2019
DOI: 10.1039/c9ra02315a
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of a novel BiPO4 phase junction with enhanced photocatalytic performance towards aniline blue degradation

Abstract: A novel BiPO4 photocatalyst has been fabricated via a facile precipitation route using dimethyl sulfoxide (DMSO) as a solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The details of the synthesis of BiPO 4 were reported in our previous study. 51 Typically, 1.94 g of Bi(NO 3 ) 3 ·5H 2 O and 0.5 g CTAB were stirred in 40 mL dimethyl sulfoxide. Then 0.524 g (NH 4 ) 2 HPO 4 dissolved in 40 mL of water was dropped into the previous solution under vigorous stirring for 1 h. After the formation of precipitate, the solid was recovered with centrifugation, and then washed with water and ethanol, and finally it was dried for 6 h at 90 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the synthesis of BiPO 4 were reported in our previous study. 51 Typically, 1.94 g of Bi(NO 3 ) 3 ·5H 2 O and 0.5 g CTAB were stirred in 40 mL dimethyl sulfoxide. Then 0.524 g (NH 4 ) 2 HPO 4 dissolved in 40 mL of water was dropped into the previous solution under vigorous stirring for 1 h. After the formation of precipitate, the solid was recovered with centrifugation, and then washed with water and ethanol, and finally it was dried for 6 h at 90 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The peaks at 501 cm −1 corresponding to bending mode of the PO 4 group and the band at 196 cm −1 could be due to O−Bi−O bending mode of vibrations. 38,39 VO 4 stretching vibrations are observed at 841 cm −1 . 40 Significant vibrations indicate the presence of metal oxide bonding, phosphate, and vanadate moiety in the YB2V2 material.…”
Section: Effect Of Simultaneous Substitution Of Both V 5+ and Bimentioning
confidence: 99%
“…Therefore, there are many experiments to improve the photocatalytic activity of BiPO 4 . For instance, it was reported that the formation of an nMBIP-mMBIP phase junction obviously enhanced the photocatalytic activity of BiPO 4 ; 22,24,25 Yang et al illustrated that BiPO 4 in combination with other materials such as graphene aerogel (GA) could also improve its photocatalytic activity and increase the degradation rate of methylene blue (MB). 26 Among the many methods to enhance the photocatalytic performance of BiPO 4 and other semiconductor photocatalysts, defect introduction and control (including intrinsic defects and doping) of photocatalysts is a widespread and usual method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are many experiments to improve the photocatalytic activity of BiPO 4 . For instance, it was reported that the formation of an nMBIP–mMBIP phase junction obviously enhanced the photocatalytic activity of BiPO 4 ; 22,24,25 Yang et al illustrated that BiPO 4 in combination with other materials such as graphene aerogel (GA) could also improve its photocatalytic activity and increase the degradation rate of methylene blue (MB). 26…”
Section: Introductionmentioning
confidence: 99%